Moral Education in History Teaching under Indonesia's Merdeka Curriculum: Challenges and Contradictions in Post-Colonial Pedagogical Reform - Fitrian Jingga Arimbi (Universitas Negeri Semarang, 2025)
This qualitative study critically examines the implementation of moral and character education within history teaching under Indonesia's Merdeka Curriculum. Drawing on interviews, observations, and document analysis at two public high schools in Kudus, Central Java, the research reveals significant gaps between curriculum policy and classroom practice. While the curriculum provides a framework, integration of character values remains suboptimal due to overemphasis on the Pancasila Student Profile project, insufficient teacher training, non-strategic scheduling, and lack of validated teaching materials. Student perspectives indicate varied and often limited reception of character education. The findings contribute to global debates on post-colonial curriculum reform, teacher agency, and the challenges of embedding moral education in history teaching. The study underscores the need for balanced, intentional pedagogical approaches to translate policy into meaningful practice, advocating for sustained professional development and context-sensitive resource development